Primary and Secondary Optic Nerve Sheath Meningioma - Solli, Elena; Turbin, Roger E. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective This study was aimed to review issues relating to the recognition, radiographic diagnosis, monitoring, and management of primary and secondary optic nerve sheath meningioma (ONSM).Design This study is a review of peer-reviewed literature combined with illustrative case studies.Participants and Methods A literature search was conducted via the PubMed database using pertinent search terms. Selected articles were limited to those written or translated into English. Additional works cited within articles were also included. Individual cases were drawn from the experience of a tertiary academic neuroophthalmic and orbital practice. Tables summarize radiotherapeutic and surgical studies, excluding single case reports and studies focusing on meningioma of intracranial origin.Main Outcome Measurements Review of reported surgical and radiotherapeutic series is the primary measurement.Results The natural history of optic nerve sheath meningiomas is primarily characterized by progressive ipsilateral vision loss. Diagnosis is typically based on radiographic imaging findings, with biopsy remaining indicated in some patients. Management strategies may include observation, radiation, and/or surgical intervention, or a combination of these approaches. The role of surgery, especially with respect to primary ONSM (pONSM), remains controversial. Advancement of radiotherapy techniques has shifted modern treatment paradigms in pONSM toward radiation as primary treatment, as surgical outcomes are inferior in major studies. Although radiation remains the treatment of choice in many cases, selected patients may benefit from surgery, especially in the setting of secondary ONSM (sONSM).Conclusion A wide variety of radiotherapeutic and surgical treatment modalities for ONSM exist. The specific indications for each management strategy continue to be redefined.
Keywords: optic nerve sheath meningioma; optic nerve tumor; orbital meningioma; orbital tumor; radiation; radiotherapy; surgery